Leadership As One Of The Needs And Personal Qualities Of A Teenager - Mambetyarov Sharyar (Euro Asian Journal Publishing, 2024)
This article focuses on the issue of leadership, provides information on various approaches, and the emergence of a leader. It also shows the difference between a leader and a leader and their place and importance in society.
Keywords: Leadership; leader; peer; knowledge